Dynamic economic load dispatch with wind energy using modified harmony search. (10th May 2010) - Pandi, V. Ravikumar; Panigrahi, B.K.; Das, Swagatam; Cui, Zhihua
The optimisation of fuel cost for short term economic dispatch of thermal generators along with renewable sources like wind generator is considered in this paper. The non-linear constraints considered are power generation limits, reserve limits and ramp rate limits. The optimal dispatch in the presence of the wind generation is obtained using modified harmony search (MHS) algorithm. The wind generator cost model is developed and used in this dynamic economic load dispatch (ELD) problem. The forecasted wind speed is utilised to calculate the average wind power output and this power is included in the economic dispatch model by means of negative load approach. Numerical results for the sample test system having five thermal units, one wind farm and one diesel unit have been presented to demonstrate the performance of the algorithm.